2013
DOI: 10.1111/exd.12148
|View full text |Cite
|
Sign up to set email alerts
|

Role of the aryl hydrocarbon receptor in tobacco smoke extract–induced matrix metalloproteinase‐1 expression

Abstract: Findings from large epidemiologic studies indicate that there is a link between smoking and extrinsic skin ageing. We previously reported that matrix metalloproteinases (MMPs) mediate connective tissue damage in skin exposed to tobacco smoke extracts. Tobacco smoke contains more than 3800 constituents, including numerous water-insoluble polycyclic aromatic hydrocarbons (PAHs) that trigger aryl hydrocarbon receptor (AhR) signalling pathways. To analyse the molecular mechanisms involved in tobacco smoke-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 30 publications
3
70
0
1
Order By: Relevance
“…But the risk of side effects from erythema to severe skin damages like invasive squamous cell carcinomas limits long-term and child treatment (1)(2)(3)(4)(5). Blue light irradiation is an UV-free alternative, but the functional mechanisms of this treatment remain elusive (6)(7)(8)(9).…”
Section: Accepted For Publication 17 June 2013mentioning
confidence: 99%
See 2 more Smart Citations
“…But the risk of side effects from erythema to severe skin damages like invasive squamous cell carcinomas limits long-term and child treatment (1)(2)(3)(4)(5). Blue light irradiation is an UV-free alternative, but the functional mechanisms of this treatment remain elusive (6)(7)(8)(9).…”
Section: Accepted For Publication 17 June 2013mentioning
confidence: 99%
“…Melanin pigmentation of the oral cavity is commonly observed among tobacco smokers, the so-called smoker's melanosis (2). Although many studies have shown that tobacco smoke causes skin ageing mediated by, for example, its effects on fibroblasts and keratinocytes (3)(4)(5), narrowing of blood vessels (6) and loss of vitamin C (7), no studies to date have directly evaluated the mechanisms underlying smoker's pigmentation. Skin pigmentation results from an increased production of melanins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tobacco smoke contains more than 3800 constituents, including numerous water-insoluble polycyclic aromatic hydrocarbons (PAHs) that trigger aryl hydrocarbon receptor (AhR) signalling pathways. To analyse the molecular mechanisms involved in tobacco smoke-induced skin aging [97].…”
Section: Effects Of Smokingmentioning
confidence: 99%
“…These findings suggest that the tobacco smoke extracts induce MMP-1 expression in human fibroblasts and keratinocytes via activation of the AhR pathway. Thus, the AhR pathway may be pathogenetically involved in extrinsic skin ageing [97].…”
Section: Effects Of Smokingmentioning
confidence: 99%